The Cost of Imported Goods Filling The Showcases: Gradual Debt Consolidation (1958-1965) - Ferhat Akyüz (Yakın Dönem Türkiye Araştırmaları)
This study focuses on debt consolidation between 1958 and 1965, with a particular emphasis on the consolidation efforts in 1960. Various types of debts in Türkiye, ranging from August 4, 1958, to 1965, were gradually consolidated, liquidated, canceled, or offset. While the majority of these debts were public debts, they also included private sector debts related to credit-based foreign trade and liquidated banks. The consolidated debts during this period exceeded the expenditure/income portion of any given year’s public budget totaling approximately 16 billion TL between 1958 and 1965. This study examines the gradual consolidation process initiated after the stability measures of 1958 and discusses the prerequisites of consolidation under the influence of economic policies from 1946 to 1958. It also highlights developments related to the 1959 consolidation agreement for credit-based foreign trade debts with the European Economic Cooperation Organization and the fundamental debt consolidation law enacted in 1960. Quantitative data on debt consolidation was primarily obtained from the proceedings of the Grand National Assembly of Türkiye. In addition, resources such as the archives of the Presidency of the Republic, the Official Gazette and periodicals were also used. The study reveals that public debts arising as a consequence of economic policies from 1946 to 1958, along with specific private sector debts, were deferred to the 1970s and 1980s through gradual debt consolidation.